Position Of Light And Water In Architecture And Philosophy Of Art - Yurtyapan Salimi, Aysegul; Salimi, Amineddin; Kara Pilehvarian, Nuran (The Turkish Online Journal of Design Art and Communication, 2016)
Light and water re key elements and indicators are in human life. Water as a lifeblood is important in views, philosophies and cultures in the world and its role is considered beyond its functional role as a symbol of purity, birth and beauty. In ancient Persia, water was a sign of lighting and purity and was so valuable. Architects have always tried to make the best possible use of the environmental resources and water that was an important element to use all the beauty and perfection of water, so water becomes a factor in order to calmness, cleansing and peace. Light reflects the effects and nature of God whose presence is manifested in architecture. Light has always been a symbol of meaning and the world kingdom. Hence, light, occupies a central place in religious architecture. Light and water were placed in contemporary architecture and philosophy and in terms of beauty, have offered outstanding works in philosophy and architecture. So in this study, we have tried to pay to the importance and application of light and water in architecture and the arts and philosophy.
Keywords: Water; Light; Architecture; Philosophy; Art